2022
DOI: 10.3390/molecules27238301
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Function of Human Jumping Translocation Breakpoint Protein (hJTB) and Its Interacting Partners through In-Solution Proteomics of MCF7 Cells

Abstract: Human jumping translocation breakpoint (hJTB) gene is located on chromosome 1q21 and is involved in unbalanced translocation in many types of cancer. JTB protein is ubiquitously present in normal cells but it is found to be overexpressed or downregulated in various types of cancer cells, where this protein and its isoforms promote mitochondrial dysfunction, resistance to apoptosis, genomic instability, proliferation, invasion and metastasis. Hence, JTB could be a tumor biomarker for different types of cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 163 publications
0
19
0
Order By: Relevance
“…Proteomics approaches based on the LC-MS/MS strategy have been used for the proteomic analyses of BCCL exosomes and have revealed disease patterns and potential biomarkers [ 201 ], as well as being used for examining BCCL-conditioned media that has shown a significant enrichment in the secreted proteins involved in BC development in comparison the corresponding cell lysates [ 319 ]. Several of our studies have investigated the effects of the overexpression [ 320 ] and downregulation [ 321 , 322 ] of the jumping translocation breakpoint (JTB) protein and its interacting partners for potential use as biomarker in BC, using an LC-MS/MS approach combined with in-gel [ 320 , 321 ], as well as the in-solution proteomics of MCF7 cells [ 322 ]. Three BCCLs, MCF10A (non-malignant), MCF7 (estrogen- and progesterone-receptor-positive, metastatic), and MDA-MB-231, have been investigated using LC-MS/MS for a phosphoproteomics-based analysis of BC-derived small EVs, in order to emphasize the disease-specific phosphorylated metabolic enzymes [ 323 ].…”
Section: Omics-based Applications In Breast Cancer Modelingmentioning
confidence: 99%
“…Proteomics approaches based on the LC-MS/MS strategy have been used for the proteomic analyses of BCCL exosomes and have revealed disease patterns and potential biomarkers [ 201 ], as well as being used for examining BCCL-conditioned media that has shown a significant enrichment in the secreted proteins involved in BC development in comparison the corresponding cell lysates [ 319 ]. Several of our studies have investigated the effects of the overexpression [ 320 ] and downregulation [ 321 , 322 ] of the jumping translocation breakpoint (JTB) protein and its interacting partners for potential use as biomarker in BC, using an LC-MS/MS approach combined with in-gel [ 320 , 321 ], as well as the in-solution proteomics of MCF7 cells [ 322 ]. Three BCCLs, MCF10A (non-malignant), MCF7 (estrogen- and progesterone-receptor-positive, metastatic), and MDA-MB-231, have been investigated using LC-MS/MS for a phosphoproteomics-based analysis of BC-derived small EVs, in order to emphasize the disease-specific phosphorylated metabolic enzymes [ 323 ].…”
Section: Omics-based Applications In Breast Cancer Modelingmentioning
confidence: 99%
“…Effects of downregulation of a specific protein in cancer cell lines and resultant proteome and interactome characterizations offer an attractive way toward identification of global changes affecting cellular behavior. Such alterations are regularly identified through strategic experimentations involving MS. 161 Knock down of EZH2 reverses tamoxifen (TMX) resistance in cell lines by affecting levels of proteins like CD44, Annexin A2, nucleosome assembly protein 1, and lamin A/C. 121 Matrix metalloproteinase-11 (MMP-11), an endopeptidase that degrades ECM, facilitates cancer development and metastasis.…”
Section: Studies Characterizing Drug Induced Proteomesmentioning
confidence: 99%
“…Cell lines are probed for drug-resistant proteomes, and potential drug responsive proteins are identified . Specific queries of protein expressions in BC cells are to be used as potential biomarkers for cancer tissues . Reports of cross “omic” studies are integrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and role of JTB in cancer are linked to the emergence, progression, and spread of different malignant tumors[36].Several research studies indicate that the amount of JTB expression is notably increased in speci c types of cancer, including breast cancer, liver cancer, and colon cancer[37][38][39].Furthermore, JTB is also implicated in biological processes like cell proliferation, invasion, and cancer cell metastasis, rendering it a promising target for therapy.According to recent research, JTB has been found to impact the ability of immune cells to function, leading to tumor immune escape. This has made it a highly discussed subject in the eld of cancer immunotherapy[40].Nevertheless, the impact of JTB on osteosarcoma remains unexplored.Based on our above research, we believe that paclitaxel can affect the biological activity of JTB by binding to the protein it encodes.JTB has a twofold impact on tumor cell division and the regulation of immune cells, particularly immune cells, consequently in uencing the prognosis of patients.…”
mentioning
confidence: 99%